URGENSI MASLAHAH DALAM KONSEP EKONOMI SYARIAH - Sakirman, Sakirman (Lembaga Penelitian dan Pengabdian pada Masyarakat (LP2M) IAIN Palopo, 2016)
The fragility of the economic system of capitalism and socialism makes the Islamic economic system into an alternative economic system and studied in depth by contemporary Islamic economic thinkers. In realizing Islamic economic system must be aligned with the maqasid al-shariah (goals sharia). There are four main approaches in the study of Islamic economics namely: a pragmatic approach, recitative, utopian and adaptive. Such an approach always leads to moral values, human brotherhood, social justice, integrating Islamic values and aims for the establishment of al-mashlahah as the core maqashid al-shariah can be used as an argument of the legal establishment, especially relating to Islamic economics. Ijtihad in Islam economy by using al-maslahah can be done by meeting certain requirements that do not conflict with al-Quran and al-Hadith and not contrary to qiyas. Besides, it does not conflict with a higher benefit, both in how to do it and in a way to preserve from extinction. Economic Ijtihad Islam implemented by analyzing the social and political realities and priorities (fiqh figh realities and priorities) in order to achieve the benefit of society and the state.